Anne of the island - Montgomery, L. M. (Lucy Maud), 1874-1942 (Montgomery, L. M. (Lucy Maud), 1874-1942. Anne of Green Gables novels, 1998)
Continues the adventures of Anne Shirley and her friends at college.